Trust, welfare states and income equality: What causes what? - Andreas Bergh; Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2013)
The cross-country correlation between social trust and income equality is well documented, but few studies examine the direction of causality. We show theoretically that by facilitating cooperation, trust may increase efficiency and lead to more equal outcomes, while the feedback from inequality to trust is ambiguous. Using a structural equations model estimated on a large country sample, we find that trust has a positive effect on both market and net income equality. Larger welfare states lead to higher net equality but neither net income equality nor welfare state size seems to have a causal effect on trust. We conclude that while trust facilitates welfare state policies that may reduce net inequality, this decrease in inequality does not increase trust.
Keywords: H10; D63; D69; 330; Social trust; Inequality; Welfare State